Severe hypercortisolism and recurring hypokalemia - Pinzon-Tovar, Alejandro (2022)
Endogenous Cushing syndrome derives from a chronic, inappropriate, and sustained increase in glucocorticoids, mainly in response to remarkably high serum concentrations of adrenocorticotropic hormone (ACTH) secreted from an adenohypophyseal tumor, Cushing's disease, or due to ectopic production by neuroendocrine tumors. Adrenal Cushing’s disease is caused by tumors of the adrenal cortex that autonomously produce cortisol and this is independent from ACTH action. Clinical course, treatment, prognosis, and possible complications depend on correctly identifying the triggering lesion; this situation frequently becomes a challenging experience for clinicians. We present the case of a 62-year-old woman, admitted for constitutional symptoms with severe hypokalemia that was difficult to correct and severe hypercortisolism.